Large Homogeneous Genome Regions (Isochores) in Soybean [Glycine Max (L.) Merr.] - Woody, Jenna L.; Beavis, William; Shoemaker, Randy C. (Frontiers in Genetics, 2012)
The landscape of plant genomes, while slowly being characterized and defined, is still composed primarily of regions of undefined function. Many eukaryotic genomes contain isochore regions, mosaics of homogeneous GC content that can abruptly change from one neighboring isochore to the next. Isochores are broken into families which are characterized by their GC levels. We identified 4,339 compositionally distinct domains and 331 of these were identified as Long Homogeneous Genome Regions (LHGRs). We assigned these to four families based on finite mixture models of GC content. We then characterized each family with respect to exon length, gene content, and transposeable elements. The LHGR pattern of soybeans is unique in that while the majority of the genes within LHGRs are found within a single LHGR family with a narrow GC-range (Family B), that family is not the highest in GC content as seen in vertebrates and invertebrates. Instead Family B has a mean GC content of 35%. The range of GC content for all LHGRs is 16-59% GC which is a larger range than what is typical of vertebrates. This is the first study in which LHGRs have been identified in soybeans and the functions of the genes within the LHGRs have been analyzed.